IMPLEMENTASI PROGRAM DAERAH PEMBERDAYAAN MASYARAKAT (PDPM) DALAM MEWUJUDKAN ”KABUPATEN TEGAL OPEN DEFECATION FREE 2019” - Yuva Naelana; S. Bekti Istiyanto (Jurnal Dakwah Tabligh, 2019)
The Community Based Total Sanitation Program (STBM) is a program launched by the Ministry of Health of the Republic of Indonesia. One of the pillars of the STBM, Open Defecation Free (ODF), is one of the homeworks of the local government. In contrast to other districts, in Tegal Regency the implementation of this program was regulated directly in the Regent's Regulation on the Regional Program for Community Empowerment. The purpose of this study is to explore further how PDPM will be implemented in an effort to realize Tegal Open Defecation Free District in 2019. The method used in the preparation of this study is descriptive qualitative. The author uses two data sources namely primary and secondary through in-depth interviews with three informants and documentation. The results show that so far the Jambanisasi PDPM has been considered successful in building public awareness of the importance of healthy sanitation. The implementation of ODF through the three main components of STBM and triggering techniques to meet the three expectations, namely right target, quality and benefits. PDPM Jambanisasi has succeeded in empowering communities in the health and economic fields through the community of sanitation entrepreneurs.